Sustainable Operations Management Advances in Strategy and Methodology - Chiarini, Andrea; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents innovative research on various aspects of sustainability in the field of operations management and illustrates the potential of sustainability thinking and practice to improve operations performance and thereby meet customer needs. Particular attention is devoted to corporate social responsibility and marketing strategy, knowledge management for sustainability, the role of culture in a sustainable built environment, sustainable manufacturing through the application of lean and green concepts, advancing sustainability through ISO standards, and the sustainable supply chain. The present decade is proving to be a time of change in terms of business strategies and operations management. Many of the trends are still subject to uncertainty, but an understanding of the need for, and benefits of, sustainability can give a clear indication of their trajectory. Consumers and markets in general believe that while implementing their business strategies, companies should also try to improve society and the environment and to exercise social responsibility toward their employees. This book provides insights into how this may be achieved, and it is recommended for researchers as well as all practitioners and managers dedicated to enhancing sustainability in operations.
Marketing strategy, strategic planning and corporate social responsibility: an exploratory research -- Sustainable knowledge management and the outsourcing of core competences-Does that fit together? Initial insights from a literature review -- The role of culture in a sustainable built environment -- The management of environmental performance in the supply chain: an overview -- The measurement of environmental performance in hospitals: a systematic review of literature -- How does innovativeness foster sustainable supply chain management? -- Sustainable manufacturing: the lean and green business model -- Sustainability through eco-design: shedding light on the adoption of the ISO 14006 standard -- Early adoption of ISO 50001 standard: an empirical study -- Sustainability in Iran$1 (Bs road transport sector: evaluating strategies and policies.s
Keywords: Economics; Sustainable development; Operations research; Business planning; Economics/Management Science; Operation Research/Decision Theory; Sustainable Development; Business Strategy/Leadership.; Organization/Planning.; Production/Logistics/Supply Chain Management; Non-Profit Enterprises/Corporate Social Responsibility